Pengaruh Lingkungan Kerja Non Fisik Dan Komitmen Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Intrinsik Sebagai Variabel Intervening - Fuad, Fadlan Ahmad; Akhmadi, Akhmadi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
This study aims to determine the effect of non physical work environment and organizational commitment to employee performance with intrinsic job satisfaction as intervening variable. The research was conducted on 100 employees of PT Paramitra Gunakarya Cemerlang selected using judgement sampling. Data were analyzed using Structural Equation Modeling (SEM) method with SmartPLS program. Based on the results of hypothesis testing shows non-physical work environment has a significant effect on employee performance. The better the non-physical work environment it can make employees produce better performance. Organizational commitment has a significant effect on employee performance. The higher organizational commitment that employees have, the higher the employee performance. Non-physical work environment has significant effect on intrinsic job satisfaction. The better condition of non physical work environment will make the higher intrinsic job satisfaction. Organizational commitment has a significant effect on intrinsic job satisfaction. The higher commitment of employees in the organization will increase employee's intrinsic job satisfaction. Intrinsic job satisfaction has a significant effect on employee performance. The higher the intrinsic job satisfaction that can be fulfilled the better the employee performance.